2015
DOI: 10.1177/1557988315621604
|View full text |Cite
|
Sign up to set email alerts
|

The Health of the Nation’s Custodial Grandfathers and Older Single Fathers: Findings From the Behavior Risk Factor Surveillance System

Abstract: Two important parent groups are solo grandfathers and single fathers raising children alone. The health of male caregivers raising children has received little attention by scholars. Investigating the health of single male caregivers raises awareness about their physical vulnerability. This study uses the 2012 Behavioral Risk Factor Surveillance System to compare health characteristics of 82 solo grandfathers with 396 single fathers aged 50 years and older. The findings suggest that grandfathers exhibited a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
8
2
Order By: Relevance
“…The demographic and health correlates of grandparents assuming the caregiving role have been wellcharacterized by previous research. Most custodial grandparents are aged 50 to 59 years 8 and, compared with parents, tend to have poorer physical [9][10][11][12] and mental [13][14][15] health before taking on the demanding role of parenting a child. Custodial grandparents may also feel isolated from peers because the demands of caregiving can be time-consuming.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The demographic and health correlates of grandparents assuming the caregiving role have been wellcharacterized by previous research. Most custodial grandparents are aged 50 to 59 years 8 and, compared with parents, tend to have poorer physical [9][10][11][12] and mental [13][14][15] health before taking on the demanding role of parenting a child. Custodial grandparents may also feel isolated from peers because the demands of caregiving can be time-consuming.…”
mentioning
confidence: 99%
“…27 Previous researchers have further explored grandparent and grandchild outcomes among subpopulations of grandparent caregivers. Analyses have individually been focused on grandmothers 15,28,29 and grandfathers 11 raising grandchildren, racial differences among grandfamilies, 10,29 the diverse cultural attitudes and outcomes of grandparenting, 14,30 and how singlegrandparent caregivers compare with single-parent caregivers. 11,12 These studies individually provide key insights into select components of the grandfamily.…”
mentioning
confidence: 99%
“…All BRFSS landline respondents 65 years and older who indicated “grandparent” to this question constituted older adults living in multigenerational family households (6.1% of the total study sample, n = 4921; N = 2,227,149) in our study. In prior studies, the BRFSS “relationship” question has been used to identify grandparent–grandchild multigenerational family structures and to investigate older adult health [ 62 , 67 , 68 , 69 ].…”
Section: Methodsmentioning
confidence: 99%
“…Female-headed households have lower health status than women in other living arrangements, and single adult fathers and custodial grandfathers face high rates of diabetes, obesity and mental health illness compared with national rates. 20,21 Family-based treatment of obesity in children that also targets weight loss in the parents has been shown to be effective for weight loss in both children and their parents, [22][23][24][25][26][27] and interventions for chronic disease management in parents may have spillover effects on adolescents. 28 Qualitative research among parents with diabetes has shown that their children's dietary preferences tempt them to eat foods that they are supposed to be avoiding.…”
Section: Introductionmentioning
confidence: 99%
“…However, family context may be an important consideration for achieving lifestyle change. Female‐headed households have lower health status than women in other living arrangements, and single adult fathers and custodial grandfathers face high rates of diabetes, obesity and mental health illness compared with national rates 20,21 . Family‐based treatment of obesity in children that also targets weight loss in the parents has been shown to be effective for weight loss in both children and their parents, 22–27 and interventions for chronic disease management in parents may have spillover effects on adolescents 28 .…”
Section: Introductionmentioning
confidence: 99%